An evaluation of synchronous reinforcement for increasing on‐task behavior in preschool children. Issue 3 (4th March 2020) - Diaz de Villegas, Sara C.; Dozier, Claudia L.; Jess, Rachel L.; Foley, Elizabeth A.
Abstract : A synchronous‐reinforcement schedule is a type of schedule of covariation in which the onset and offset of the reinforcer covaries with the onset and offset of behavior. This study was a proof‐of‐concept demonstration of the efficacy of synchronous reinforcement for on‐task behavior (completing a preacademic skill) and an evaluation of preschoolers' preference for this schedule in comparison to a more traditional schedule of reinforcement. Specifically, we compared the effects of a synchronous‐reinforcement schedule to one in which continuous access to stimuli was delivered at the end of the session and yoked to the duration of on‐task behavior that occurred during the session (accumulated reinforcement). Results showed the synchronous‐reinforcement schedule was more effective for increasing on‐task behavior and preferred by most participants.